Natural Aphrodisiacs—A Review of Selected Sexual Enhancers. Issue 4 (15th July 2015) - West, Elizabeth; Krychman, Michael
Abstract Introduction The Food and Drug Administration defines an aphrodisiac drug product as "any product that bears labeling claims that it will arouse or increase sexual desire, or that it will improve sexual performance." Presently, there are no approved medications for the treatment of lowered desire for women, and many opt for "natural" products. Aim The aim of this article was to review the most popular and currently used aphrodisiac products marketed in the United States. The safety and efficacy of animal‐ and plant‐based aphrodisiacs, vitamins and minerals, and popular over‐the‐counter combination supplements have been reviewed. Methods An English PubMed literature search was performed using the key words "sexuality, " "sex, " "aphrodisiac, " and "sexual enhancer." Approximately 50 articles were reviewed by the authors. The authors used relevant case series, case‐controlled, and randomized clinical trial data. Main Outcome Measures Products were evaluated based on the quality of research, and their known efficacy and safety considerations. Products with low risk and potential benefit for sexual response based on prior research studies were highlighted. Results Research has demonstrated that the risks of yohimbine, Spanish fly, mad honey, and Bufo toad may outweigh any benefit, and these products should be avoided. Other products, such as Maca, Tribulus, Ginkgo, and ginseng, have limited but emerging data. Randomized clinical trial data are often lacking, but future research should be performed to further elucidate the efficacy and safety of these products. Conclusion Future randomized clinical trials are warranted before health care practitioners can recommend most aphrodisiac products. There remain some medical concerns with drug interactions, purity, reliability, and safety. West E and Krychman M. Natural aphrodisiacs—A review of selected sexual enhancers. Sex Med Rev 2015;3:279–288.